2003
DOI: 10.1603/0046-225x-32.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Overwintered Boll Weevils (Coleoptera: Curculionidae) in Relation to Microclimatic Factors

Abstract: The boll weevil, Anthonomus grandis Boheman, enters a diapause state to survive winters in temperate regions and subsequently emerges from overwintering habitats to infest squaring cotton in the spring. Previous research has found that boll weevil overwintering emergence is closely associated with climatic patterns of temperature and precipitation. The objectives of this study were to determine the effects of temperature, humidity, and other meteorological factors on the temporal pattern of boll weevil emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The higher host-free survival rates of males compared with females are difficult to interpret unambiguously, especially considering that several previous studies using either vegetative stage cotton as food ( Esquivel et al 2004 , Suh and Spurgeon 2006 ) or observations of survival under ambient conditions ( Westbrook et al 2003 , Spurgeon 2008 ) did not report similar differences. Regardless, differences observed in this study occurred early in the host-free survival period.…”
Section: Discussionmentioning
confidence: 90%
“…The higher host-free survival rates of males compared with females are difficult to interpret unambiguously, especially considering that several previous studies using either vegetative stage cotton as food ( Esquivel et al 2004 , Suh and Spurgeon 2006 ) or observations of survival under ambient conditions ( Westbrook et al 2003 , Spurgeon 2008 ) did not report similar differences. Regardless, differences observed in this study occurred early in the host-free survival period.…”
Section: Discussionmentioning
confidence: 90%
“…However, their feeding period duration was too long (48 d) to produce a good estimate of potential host-free longevity because many of the weevils that did not enter diapause would have died before the end of the feeding period. Most other studies of overwintering survival have been conducted under uncontrolled field conditions or used a mixture of food types ( Fenton and Dunnam 1927 ; Gaines 1959 ; Rummel and Carroll 1983 ; Carroll et al 1993 ; Parajulee et al 1996 , 1997 ; Westbrook et al 2003 ; Spurgeon 2008 ), so comparisons with our results are not possible. In contrast, Spurgeon and Suh (2017) fed a cotton boll diet similar to the diet we used, and observed host-free survival at 23.9°C that was very similar to the survival we observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Taub-Montemayor et al (1997) produced putative diapausing weevils by exposing unfed newly-emerged weevils to a photoperiod of 12:12 h and a thermoperiod of 26:21°C [L:D], but none of the weevils survived beyond 10 d. Finally. Spurgeon and Raulston (1998a) and Spurgeon and Esquivel (2000) found that feeding regimen could be manipulated to control the diapause response, and their techniques were used to produce high levels of overwintering survival (45-73%) in field studies (Westbrook et al 2003), and to identify and characterize a storage protein diagnostic of diapause in boll weevils (Lewis et al 2002). Spurgeon et al (2003) suggested that failure to recognize the respective fat body types characteristic of newly eclosed, reproductive, and diapausing weevils has likely contributed to confusion in the literature.…”
Section: Discussionmentioning
confidence: 99%